Penerapan Metode Simple Columnar Transposition (SCTR) untuk Aplikasi Enkripsi Teks Berbasis Android - Bramantara Yudha (Teknik Informatika Universitas Pamulang, 2021)
The development of communication technology such as the use of mobile phones based on android. Android has the capability of getting good as personal computer and it has a large storage area. Android users use it to store important data. Critical data that is stored to make various ways to membobolnya. The role of cryptography is indispensable for securing the data. Cryptography is the science to encode a message, while to keep the message or document is secure and cannot be read by those who are not entitled to use encryption. The application of encryption uses a symmetric algorithm. On the application of this method used is Simple Columnar Transposition method. Simple Columnar Transposition method by dividing plainteks into blocks with a key length (k) certain then these blocks are arranged in the form of rows and columns. The making of this application using the JAVA programming language and XML. The application is made for a mobile with Android using the Studio. This application was eventually shown on android mobile phone users. The application used to encode text/sentence, the result of encryption in the form of chipertext, and the result of decrypting plaintext form.